The Influence of Product Quality, Price, and Celebrity Endorsers on Decisions Purchase Wardah Beauty Products at The Lariss Store Tlogosari City Semarang - Muazidah, Siti; Purwanto, Edy (Economics and Business International Conference Proceeding, 2024)
This research aims to determine the influence of product quality, price,and celebrity endorsers on the best-selling Tlogosari store.The population in this research is consumers who buy Wardah products at the Lares Tlogosari store, the number of which is not known for certain. The sampling technique uses non-probability sampling, where the sample does not provide a chance of being selected as a member of the sample.Based on the results of the analysis, it shows that the Product Quality variable (X1) has a positive and insignificant effect on purchasing decisions (Y), price (X2) has a positive and significant effect on purchasing decisions (Y), Celebrity Endorser (X3) has a negative and insignificant effect on decisions. Purchase (Y), then simultaneously and together it can be concluded that Product Quality (X1), Price (X2) and Celebrity endorser (X3) have a positive and significant effect on purchasing decisions (Y).